2016
DOI: 10.7314/apjcp.2015.16.18.8473
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices Regarding HPV Vaccination Among Medical and Para Medical in Students, India a Cross Sectional Study

Abstract: Background: High risk human papilloma virus (HPV) types 16 and 18 have been proven as central causes of cervical cancer and safety and immunogenicity of HPV vaccines are sufficiently established. Knowledge and practices of HPV vaccination among medical and paramedical students is vital as these may strongly determine intention to recommend vaccination to others in the future. The present study was therefore undertaken to assess the knowledge, attitude and practices regarding cervical cancer screening and HPV v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
61
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 30 publications
13
61
4
2
Order By: Relevance
“…The percentage of heard about cervical cancer was 96.8% and it was expressed as percentage and it was more in female participants and was concurrent with a study done by swarnapriya et al [6] . However their knowedge was lower than that observed in a study among female health workers in a teaching hospital in northern Nigeria where 98.6% of female health workers had good knowledge about cervical cancer [8].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The percentage of heard about cervical cancer was 96.8% and it was expressed as percentage and it was more in female participants and was concurrent with a study done by swarnapriya et al [6] . However their knowedge was lower than that observed in a study among female health workers in a teaching hospital in northern Nigeria where 98.6% of female health workers had good knowledge about cervical cancer [8].…”
Section: Discussionsupporting
confidence: 79%
“…In this current study the percentage of male participants was found to be more (50.3%)when compared to female (49.7%) and it may vary between the studies .A study conducted by swarnapriya et al [6] found that female preponderance and it is dissimilar from the current study.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…A recent study conducted at a tertiary institution reported that 9.8 percent of Singaporean women aged between 15 and 22 years had received an HPV vaccine [25]. A cross-sectional study conducted among medical and para-medical students in 2014 also showed better HPV vaccination rates in India; 6.8 percent of Indian college women and men had received the vaccine [26]. At the global level, it is estimated that 39.7 percent of targeted women (between 9 and 45 years) have been vaccinated worldwide [27].…”
mentioning
confidence: 99%
“…Overall, 77 papers and one dissertation were eligible for analysis and were listed in the order of publication years. [171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788899091929394] The review process is explained in Figure 1.…”
Section: Methodsmentioning
confidence: 99%